The Impact of Digital Era 4.0 Transformation on Human Resources Management - Amalia, Mei Rani (Penelitian dan Pengembangan Ilmu, 2024)
The rapid digital revolution has changed the paradigm of human resource management in the context of the digital era 4.0. This article presents the results of a systematic analysis of literature which aims to explain the influence of the digital revolution on Human Resource Management). A total of 20 selected journal articles were used as the basis for the research, focusing on main themes such as the transformation of the role of Human Resource Management), human resource management strategies for sustainability, and digital-based human resource management concepts. The results of a systematic analysis of literature highlight the key role of Human Resource Management as a strategic partner in facing organizational transformation in the digital era 4.0. The concept of digital-based human resource management is in the spotlight, emphasizing the importance of developing digital skills among the workforce. In addition, the findings show that Human Resource Management) plays an important role in a company's sustainability strategy, integrating economic, social and environmental aspects.